If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F * 0 = 6 * 0 + -1 Reorder the terms for easier multiplication: 0F = 6 * 0 + -1 Anything times zero is zero. 0F = 6 * 0 + -1 Multiply 6 * 0 0 = 0 + -1 Anything times zero is zero. 0 = 0 + -1 Combine like terms: 0 + -1 = -1 0 = -1 Solving 0 = -1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5xn-20=8 | | 14=1.5(7) | | 6(6+68)= | | n+36=56 | | 12s-12=9s-8 | | 6x+6=4x-2 | | 60x-60=144 | | n*5=95 | | 4m^2-227m-40=0 | | n-2=180 | | 3x-2=6+4x | | -24/8 | | s+s+6=214 | | (5x+3)+32=90 | | (x-6)+2x=180 | | -4x-4=2x+8 | | 17-2x=0 | | 6x-5=38 | | (6x+2)+(2x+8)=90 | | 2x-2=6+4x | | .66+.5=4+.33w | | (3x+1)+(x+9)=90 | | 4x-2=-x+6 | | 200/20*5+20-20 | | 4x/13=16 | | x-9/6=7 | | s+s+2=214 | | -17=-32-3/5M | | -13+30= | | n+30=44 | | 1/2(6p+8)-7+2p | | -(6y+2)-(-5y-6)=3 |